2013
DOI: 10.1088/0004-637x/768/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance of the Hr 8799 Exosolar System. I. Near-Infrared Spectroscopy

Abstract: We obtained spectra in the wavelength range λ = 995-1769 nm of all four known planets orbiting the star HR 8799. Using the suite of instrumentation known as Project 1640 on the Palomar 5 m Hale Telescope, we acquired data at two epochs. This allowed for multiple imaging detections of the companions and multiple extractions of low-resolution (R ∼ 35) spectra. Data reduction employed two different methods of speckle suppression and spectrum extraction, both yielding results that agree. The spectra do not directl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
185
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 90 publications
(209 reference statements)
6
185
3
Order By: Relevance
“…Despite having incredible similarity in color and magnitude, these two objects have quite different spectral shapes. Overall, observations of young brown dwarfs and directly-imaged exoplanets (Gauza et al 2015) and HR 8799b (Barman et al 2011Oppenheimer et al 2013). The J − H color and absolute J -band magnitude of VHS 1256−1257B agree (to within the uncertainties) with photometry of the exoplanet, HR 8799b.…”
Section: Introductionsupporting
confidence: 55%
“…Despite having incredible similarity in color and magnitude, these two objects have quite different spectral shapes. Overall, observations of young brown dwarfs and directly-imaged exoplanets (Gauza et al 2015) and HR 8799b (Barman et al 2011Oppenheimer et al 2013). The J − H color and absolute J -band magnitude of VHS 1256−1257B agree (to within the uncertainties) with photometry of the exoplanet, HR 8799b.…”
Section: Introductionsupporting
confidence: 55%
“…For fainter objects, such as the planets around the star HR 8799 (Marois et al 2008b), SPHERE would be able to detect HR 8799d, 7 M Jup planet at a distance of 27 AU (Marois et al 2010;Oppenheimer et al 2013), with a relative astrometric error of 3 mas. Esposito et al (2013), using LBT/PISCES, found an astrometric error of 10 mas.…”
Section: Discussionmentioning
confidence: 99%
“…On this datacube we used both the spectral deconvolution (SD, see e.g, Sparks & Ford 2002;Thatte et al 2007) and the principal component analysis (PCA, see, e.g, Amara & Quanz 2012;Soummer et al 2012;Oppenheimer et al 2013) reductions A85, page 4 of 13 methods. For more details, regarding the first method applied on SPHERE-IFS data we refer the reader to Mesa et al (2014).…”
Section: Data Reduction and Detection Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oppenheimer et al 2013;Allers & Liu 2013). This produces large scatter in the colours, with low-gravity objects -such as the late-L-type planet 2M1207b (Chauvin et al 2004) -usually having redder J−K colours.…”
Section: Discussionmentioning
confidence: 99%